2017
DOI: 10.1038/hdy.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

The effects of outbreeding on a parasitoid wasp fixed for infection with a parthenogenesis-inducing Wolbachia symbiont

Abstract: Trichogramma wasps can be rendered asexual by infection with the maternally inherited symbiont Wolbachia. Previous studies indicate the Wolbachia strains infecting Trichogramma wasps are host-specific, inferred by failed horizontal transfer of Wolbachia to novel Trichogramma hosts. Additionally, Trichogramma can become dependent upon their Wolbachia infection for the production of female offspring, leaving them irreversibly asexual, further linking host and symbiont. We hypothesized Wolbachia strains infecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…These lines are not infected with Wolbachia: virgin females produce only male offspring. Species identification and Wolbachia infection status were confirmed using molecular methods, as described previously [28,[71][72][73].…”
Section: Trichogramma Lines and Rearingmentioning
confidence: 99%
See 2 more Smart Citations
“…These lines are not infected with Wolbachia: virgin females produce only male offspring. Species identification and Wolbachia infection status were confirmed using molecular methods, as described previously [28,[71][72][73].…”
Section: Trichogramma Lines and Rearingmentioning
confidence: 99%
“…We introgressed the sexual CA9 nuclear genome into the asexual ES865 cytoplasm, and the sexual CA29 nuclear genome into the asexual Insectary cytoplasm (Fig 1A). These pairs were chosen based on the ability to differentiate them at the A9 microsatellite locus, a size-diagnostic amplicon routinely used for identifying unique isofemale lines of this wasp [71]. For example, the Insectary line has an A9 microsatellite of 312 bp in length, and the CA29 line has an PLOS PATHOGENS A9 microsatellite of 220 bp in length-allowing us verify fertilization during introgression: a critical step because Wolbachia induces diploidization of unfertilized eggs, and thus female offspring are produced from both fertilized and unfertilized eggs [16].…”
Section: Introgression Of Wolbachia Into Sexual Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manuscript to be reviewed Alternatively, Wolbachia-mitochondria interactions may play a role in the observed fitness deductions observed for the horizontally transferred lines. Recent results with Trichogramma pretiosum showed that nuclear introgression of novel genetic background appeared to have no negative fecundity fitness effects (Lindsey & Stouthamer 2017b). However, horizontal transfer of Wolbachia was not possible with T. pretiosum, unlike here where Wolbachia were experimentally transferred to novel host nuclear and mitochondrial backgrounds.…”
Section: Discussionmentioning
confidence: 65%
“…Alternatively, Wolbachia– mitochondria interactions may play a role in the observed fitness deductions observed for the horizontally transferred lines. Recent results with T. pretiosum showed that nuclear introgression of novel genetic background appeared to have no negative fecundity fitness effects ( Lindsey & Stouthamer, 2017b ). However, horizontal transfer of Wolbachia was not possible with T. pretiosum , unlike here where Wolbachia were experimentally transferred to novel host nuclear and mitochondrial backgrounds.…”
Section: Discussionmentioning
confidence: 99%